Trends in coronary artery disease mortality among hyperlipidemic patients: Geographic, gender, and racial insights from CDC WONDER data (1999–2020) - Muhammad Abdullah Naveed; Sivaram Neppala; Himaja Dutt Chigurupati; Bazil Azeem; Ahila Ali; Faizan Ahmed; Sabin Zafar; Muhammad Omer Rehan; Rabia Iqbal; Manahil Mubeen; Hassaan Abid; Anum Mubasher; et al. (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Coronary artery disease (CAD) in hyperlipidemia is a significant cause of mortality among adults in the United States. This study investigates trends in CAD-related mortality in hyperlipidemia among adults aged 25 and older, focusing on geographic, gender, and racial/ethnic disparities from 1999 to 2020. Methods: A retrospective analysis was conducted using the CDC WONDER database from 1999 to 2020. Age-adjusted mortality rates (AAMRs), annual percent change (APC), and average annual percentage change (AAPC) were calculated per 100,000 persons, stratified by year, sex, race/ethnicity, and geographical region. Results: Between 1999 and 2020, CAD in hyperlipidemia led to 407,667 deaths among US adults aged 25+. The AAMR for CAD in hyperlipidemia rose from 4.1 in 1999 to 12.1 in 2020, with an AAPC of 4.44 (95 % CI: 3.69 to 5.48, p < 0.000001). Men had higher AAMRs (12.4) than women (5.6), with significant increases for both sexes over time. Racial/ethnic disparities showed the highest AAMRs in Whites (8.9), followed by American Indians/Alaska Natives (8.6). Geographically, AAMRs varied from 3.8 in Alabama to 16.0 in Vermont, with the Midwest showing the highest rates (9.7). Nonmetropolitan areas exhibited higher AAMRs (9.6) than metropolitan areas (8.3), with a more significant increase in nonmetropolitan areas (AAPC: 5.82, p < 0.000001). Conclusion: This study highlights significant disparities in CAD in hyperlipidemia-related mortality among US adults by race, gender, and geography. The overall increase in AAMRs from 1999 to 2020 underscores the need for targeted public health interventions to address these growing inequities.